CULTURAL SPECIFICATION OF CHINESE AMERICAN LITERATURE (Academicia Globe: Inderscience Research, 2022)
American literature is considered to be one of the most important part of the world literature, it brought many masterpieces by talented and outstanding authors. Each period of it is rich in great writers and their works which reflected the life of the nation of that time.